Identifying factors affecting comfort workwear for mountain tourism - Nurbay, Saule; Usenbekov, Zhaksybek; Seitov, Bulat; Sarttarova, Lazzat; Seitova, Nazima (Eastern-European Journal of Enterprise Technologies, 2023)
The quality and comfort of clothing for people engaged in mountain tourism are influenced by the pack of clothing materials, which determine their durability and heat resistance. In practice, wear resistance and thermal insulation of clothing materials are evaluated by standard methods for single-layer materials. To solve the problem of studying the wear resistance and heat resistance of a clothing pack, we developed an experimental setup for studying the wear resistance of the clothing pack under the influence of cyclic loads and an installation for determining the heat-shielding properties of the pack of clothing materials, allowing you to reproduce both the temperature of the underwear space, as well as environmental factors. By studying the influence of wind flow, humidity and ambient temperature on the heat-shielding ability of packages of various compositions, the most rational package of clothing for mountain tourism was determined. The selected package provides a comfortable state of a person in the absence of air permeability and at a wind speed of 5 m/s; and at wind speeds of 10 m/s and 15 m/s, the temperature of the underwear space decreases. The heat protection of the clothing package is influenced by the breathing of the athlete’s body during movements. So, at ambient temperature Tok=20 °C and humidity within 60‒70 % when the breathing simulator was turned on in the underwear space, Tpp=26 °C, W=62 %, and when it was turned off, Tpp=27 °C, and the humidity value did not change. The developed experimental installations and research methods can be recommended for use at the design stage in the production laboratories of enterprises producing mountain sports clothing